2005
DOI: 10.4000/quaternaire.418
|View full text |Cite
|
Sign up to set email alerts
|

Middle and Upper Pleistocene fluvial evolution of the Meurthe and Moselle valleys in the Paris Basin and the Rhenish Massif

Abstract: The terrace systems of the River Meurthe (Me), and the River Moselle (M) downstream from the present Moselle-Meurthe confluence are composed of eight stepped alluvial terraces (Me8-M8 to Me1-M1), situated at less than 90 m above the modern floodplain Me0-M0. Morphological, mineralogical and petrographical studies evidence that the oldest five terraces (Me8-M8 to Me4-M4) were formed by the "Palaeo-Meurthe", while the Upper Moselle flowed towards the Meuse valley. Downstream from the confluence, the three younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…These age estimates are in good agreement with the expected ages for sediments from below terrace M1, which was assumed to have been formed during MIS 2, since the upper terrace M2 is allocated to MIS 4-3 and the present floodplain M0 has a Lateglacial to Holocene age (MIS 1, Cordier et al, 2005;. These results indicate that the main terrace incision took place at the warm-tocold transition (e.g.…”
Section: Age Estimates and Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…These age estimates are in good agreement with the expected ages for sediments from below terrace M1, which was assumed to have been formed during MIS 2, since the upper terrace M2 is allocated to MIS 4-3 and the present floodplain M0 has a Lateglacial to Holocene age (MIS 1, Cordier et al, 2005;. These results indicate that the main terrace incision took place at the warm-tocold transition (e.g.…”
Section: Age Estimates and Discussionsupporting
confidence: 78%
“…While the first analyses mostly focused on the determination of numerical ages (Cordier et al, 2005;, our new research carried out at the LIAG in Hannover made it possible to develop a methodological robust basis for the luminescence dating of fluvial samples from the Moselle basin. More accurate and precise D e values have been obtained by incorporating thorough performance tests (preheat plateau, dose-recovery tests, and fading correction for feldspars) for the SAR protocol, and by using small aliquots (in spite of large aliquots) including statistical models to select the appropriate D e values from well-bleached grains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The older lower terrace most likely covers older terrace sediments but cannot be distinguished from older deposits owing to the lack of an appropriate dating method. Cordier et al (2005Cordier et al ( , 2006 found evidence for a third ''Lower Terrace'' along the river Moselle, as the main tributary of the Rhine in the Middle Rhine area, which most likely accumulated during the early Pleniglacial. The older lower terrace most likely correlates to the Last Pleniglacial and/or Late Glacial.…”
Section: Discussionmentioning
confidence: 98%